2020
DOI: 10.1177/1758835920917558
|View full text |Cite
|
Sign up to set email alerts
|

Predicting STAT1 as a prognostic marker in patients with solid cancer

Abstract: Background: Aberrant activities of signal transducer and activator of transcription 1 (STAT1) have been implicated in cancer development. However, the prognostic value of STAT1 remains unclear. This report identified the role of STAT1 in prognosis in patients with solid cancer through open literature and The Cancer Genome Atlas (TCGA) database. Methods: Published articles were obtained from PubMed, Web of Science, and Embase databases according to a search strategy up to October 2019. Pooled hazard ratios (HRs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 63 publications
(77 reference statements)
0
22
0
Order By: Relevance
“…However, studies on colorectal cancer ( Crncec et al, 2018 ) and other breast cancers ( Varikuti et al, 2017 ) found that TAT1 may act as a tumor suppressor. Even a recent meta-analysis of TAT1 in multiple types of tumors reported that the prognostic factor of STAT1 still depends on cancer type ( Zhang et al, 2020 ). From this IRG–TF regulatory network, we can see that in cervical cancer, STAT1 positively regulates low-risk IRGs ( PSME2 , LTA , and PTPN6 ), but STAT1 positively regulates high-risk IRGs ( OAS1 ) in endometrial cancer, suggesting that transcription factor STAT1 may play different biological roles in these two types of cancers.…”
Section: Resultsmentioning
confidence: 99%
“…However, studies on colorectal cancer ( Crncec et al, 2018 ) and other breast cancers ( Varikuti et al, 2017 ) found that TAT1 may act as a tumor suppressor. Even a recent meta-analysis of TAT1 in multiple types of tumors reported that the prognostic factor of STAT1 still depends on cancer type ( Zhang et al, 2020 ). From this IRG–TF regulatory network, we can see that in cervical cancer, STAT1 positively regulates low-risk IRGs ( PSME2 , LTA , and PTPN6 ), but STAT1 positively regulates high-risk IRGs ( OAS1 ) in endometrial cancer, suggesting that transcription factor STAT1 may play different biological roles in these two types of cancers.…”
Section: Resultsmentioning
confidence: 99%
“…Liquid biopsy work in the RCC field has brought attention to potential prognostic biomarkers detailing overall survival and disease outcome in patients. [6,15,[19][20][21][22] The study of EVs within RCC, while limited, has followed a similar route. It is hypothesized that tumor derived EVs may promote disease progression and metastasis, indicating poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…STAT1 has been linked to poor prognosis and, specifically within RCC, lowered overall survival rates in patients with solid tumors. [22] The ideal RCC biomarker would be present in biofluid EV samples and tumor derived EVs, but absent in tumor adjacent tissue derived EVs. As such, any mRNA transcripts that were detected in the tumor adjacent EV samples were excluded as potential diagnostic biomarkers for ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…For lung tumor multiplicity and progression phenotypes, the major association peaks were detected in chromosomes 1, 8, and 17. The region we mapped approximately at 50 Mb in chromosome 1, overlaps the region that spans the Scc20 QTL which harbors the transcription factors Stat1 and Stat4 involved in the transcription of cytokines and angiogenic factors in lung tumors [ 20 ]. These mediators might also contribute to inflammation and colon tumor development, as observed by the significant association of SNPs mapping in this region with colon tumors; the region in chromosome 8 at 54 Mb harbors the Vegf -C (vascular endothelial growth factor C) gene which is the main regulator of angiogenesis in the process of tumor growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%